The Presence of Pseudo-nitzschia australis in North Atlantic Aquaculture Sites, Implications for Monitoring Amnesic Shellfish Toxins - Callum Whyte; Sarah C. Swan; Andrew D. Turner; Robert G. Hatfield; Elaine Mitchell; Shannon Lafferty; Nadine Morrell; Stepahanie Rowland-Pilgrim; Keith Davidson (Toxins, 2023)
The farming of shellfish plays an important role in providing sustainable economic growth in coastal, rural communities in Scotland and acts as an anchor industry, supporting a range of ancillary jobs in the processing, distribution and exporting industries. The Scottish Government is encouraging shellfish farmers to double their economic contribution by 2030. These farmers face numerous challenges to reach this goal, among which is the problem caused by toxin-producing microplankton that can contaminate their shellfish, leading to harvesting site closure and the recall of product. Food Standards Scotland, a non-ministerial department of the Scottish Government, carries out a monitoring programme for both the toxin-producing microplankton and the toxins in shellfish flesh, with farms being closed when official thresholds for any toxin are breached. The farm remains closed until testing for the problematic toxin alone, often diarrhetic shellfish toxin (DST), shows the site to have dropped below the regulatory threshold. While this programme has proved to be robust, questions remain regarding the other toxins that may be present at a closed site. In this study, we tested archival material collected during site closures but only tested for DSTs as part of the official control monitoring. We found the presence of amnesic shellfish toxin (AST) in low concentrations in the majority of sites tested. In one case, the level of AST breached the official threshold. This finding has implications for AST monitoring programmes around Europe.